Analisis Yuridis Tentang Penjatuhan Pidana Kepada Pelaku Pelecehan Secara Verbal “Catcalling” di Indonesia - Rahman, Muhammad Ghazali; Tista, Adwin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research elaborates on the perspective of criminal law regarding the imposition of punishment on perpetrators of catcalling or verbal harassment, where communication occurs between the perpetrator and the victim in public spaces in the form of verbal expressions through whistling or utterances about the form of clothing, body, using indecent words and can lead to sexual violence, with the presence of the Sexual Violence Crime Law (UU TPKS) on April 12, 2022, it is hoped that it will provide protection for victims of verbal sexual harassment while providing commensurate criminal sanctions to perpetrators, where previously sanctions for perpetrators of verbal sexual harassment (Catcalling) were subject to Article 281 paragraph (2), Article 289 of the Criminal Code, Article 8 in conjunction with Article 34, Article 9 in conjunction with Article 35 of Law Number 44 of 2008 concerning Pornography, and Article 5 of the Criminal Act of Sexual Violence (UU TPKS) Number 12 of 2022. The method used in this research is a normative study which focuses on laws and regulations relating to acts of verbal sexual harassment (catcalling) in Indonesia. At the end of this research, conclusions can be drawn about the types of verbal harassment (catcalling) which can be categorized as criminal acts that fulfill the elements of a criminal act as stated in statutory regulations, and whether they are sufficient to ensnare and impose punishment on the perpetrators of the crime. criminal verbal sexual harassment (catcalling).